Ageing population in developed countries: a study of process and phenomena - Abdullah @ Chuah Hock Leng, Osman (2014)
The agcing proccss is associatcd with incrcasing lifc expcctancy in thc community and it means more and more people are going to require more health care and maintenance. In keeping pace with demographic changes, the number of places taken in residential care homes, nursing homes and hospitals are on the rise. In order to develop new health care treatments and management strategies of an elderly populatiorg a clear in{epth rmderstanding of the proccss and phenomena of the aging population is urgently required. Accordingly, this research attempts to deal with the consequences of the elderly population by studying tlre process and phenomena of aged population in developed counties.